2009
DOI: 10.1073/pnas.0902031106
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant epithelial morphology and persistent epidermal growth factor receptor signaling in a mouse model of renal carcinoma

Abstract: The epidermal growth factor receptor (EGFR) has frequently been implicated in hyperproliferative diseases of renal tubule epithelia. We have shown that the NF2 tumor suppressor Merlin inhibits EGFR internalization and signaling in a cell contact-dependent manner. Interestingly, despite the paucity of recurring mutations in human renal cell carcinoma (RCC), homozygous mutation of the NF2 gene is found in Ϸ2% of RCC patient samples in the Sanger COSMIC database. To examine the roles of Merlin and EGFR in kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Then, DESI-MSI was used to examine the changes in relative abundances of specific metabolites in RCC and control kidney in situ (32,35). Metabolites of the glutaminolytic pathway, including glutamate and α-ketoglutarate, were identified, as well as an increase in relative abundances of ions corresponding to citrate, pyruvate, malate, and succinate in RCC compared with control samples.…”
Section: Significancementioning
confidence: 99%
“…Then, DESI-MSI was used to examine the changes in relative abundances of specific metabolites in RCC and control kidney in situ (32,35). Metabolites of the glutaminolytic pathway, including glutamate and α-ketoglutarate, were identified, as well as an increase in relative abundances of ions corresponding to citrate, pyruvate, malate, and succinate in RCC compared with control samples.…”
Section: Significancementioning
confidence: 99%
“…In this connection, a report of conditional knock-out mice of the Nf2 gene in the proximal convoluted tubules is noteworthy, because 100% of these mice developed RCC within 6 -10 months. 36 The NF2 gene is responsible for neurofibromatosis type 2, a familial cancer affected by bilateral eighth-cranial-nerve tumors, as well as meningiomas, shwannomas and gliomas. The NF2 gene encodes an actin-binding protein, merlin, which shows significant homology with ezrin, radixin and moesin, in addition to the 4.1 family proteins.…”
mentioning
confidence: 99%
“…More recently, the McClatchey lab has shown that inactivation of Nf2 flox alleles in the visceral endoderm driven by a specific Villin-Cre transgene induced an important lethality ranging from E17 to postnatal day 3. About 10% of the Villin-Cre;Nf2 flox/flox surviving pups developed kidney neoplasia (36). These data show that, depending on the site and time, Nf2 inactivation could either be pro-apoptotic or promote cell proliferation.…”
Section: Nf2mentioning
confidence: 71%